Regional and local phenomena influencing the thermal state in the Flysch belt of the northeastern part of Slovakia - MAJCIN, Dušan; BILČÍK, Dušan; KUTAS, Roman; HLAVŇOVÁ, Petra; BEZÁK, Vladimír; KUCHARIČ, Ľudovít (Contributions to Geophysics and Geodesy, 2014)
The locality of the northeastern most part of Slovakian Flysch belt belongsto interesting areas in terms of the interpretation of geothermal conditions in mutualrelation with the lithosphere structure and their tectonic development. The evaluationof the geothermal energy sources parameters of this locality is likewise worthwhile. Theregion under study has the centre in position of the borehole Zboj ZB-1 and spreads outSlovakia also in Poland and Ukraine.Our contribution provides the analyses of existing geothermal data enhanced by theconstruction of temperature field models corresponding to the global and local aspects thatinfluence the temperature and heat flow density distributions. The analyses are related tothe structures and effects of separate phenomena along as well as across the Carpathianarc. The model calculations were carried out both by analytical and numerical methodsof solving the heat transfer equations including their steady state forms and transientcases too.Besides the regional trend of thermal activity decrease in direction from East-SlovakianBasin to the outer Carpathian units the combined local influences are applied: subsurfacethermophysical parameters of rock complexes distributions, non-stationary sources fromsupposed subvolcanic bodies in close surroundings of borehole Zboj ZB-1, and the effectsof the hydrological factors. Considering the observed higher thermal activity in archedzone along the Carpathian structures we discussed the thermal effects of rock complexessupposed as a source of regional Carpathian Conductivity Anomaly and the transfer ofheat from East-Slovakian Basin to Outer Carpathian Flysch units. The analysis and themodelling results suggest that the mentioned activity is caused by the influences of sourcetype phenomena mainly related to deep fault systems at the margin of the EuropeanPlatform.